KARAKTERISASI TINGKAT KEJELASAN PERCAKAPAN DAN SIFAT DIFUSI DI RUANG KELAS STUDI KASUS RUANG TVST DAN RUANG 9019 INSTITUT TEKNOLOGI BANDUNG - , RESOL SOFI IYAH, Sentagi Sesotya Utami, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Classroom and auditorium are space facilities that are generally known as learning spaces. In the process of learning, speech communication is a major activity. The standard ANSI-ASA: S12.60-2002 is a standard for acoustic classroom. This standard describes the measurement procedures and criteria for achieving good acoustic quality in the learning spaces. A frequent problem encountered related to the activity of speech communication in classrooms is the conversation clarity. One of the solutions in order to achieve this condition is by having a diffuse room, a condition where the sound energy is scattered within the same quality throughout the space. Clarity conversation is affected by the noise level and reverberation time. A case study conducted in two rooms with the same geometry, but differ in the use of absorption panels. This study measures the quality of speech intelligibility using acoustic parameters, namely T30, C50, RASTI, and background noise with the room impulse response recording method using omnidirectional loudspeaker dodecahedron and received by two microphones for subsequent data were processed using the Realtime Analyzer software. The level of sound diffusion in the room can be seen from the value of coherence (similarity) between two impulse response signals using Matlab calculations. The results of this study are 9019 rooms have reverberation time in the range of 0.8 to 1.2 s, 31.52 dB background noise, C50 -4.99 to 3.46 dB, RASTI 0.55 to 0.62, coherence 0.234 to 0.391, while TVST rooms have reverberation time in the range of 0.5 to 0.8 s, 26.96 dB background noise, C50 -2.6 to 8.89 dB, RASTI 0.61 to 0.75, coherence 0.218 to 0.419. These results provide evidence that the acoustical treatments in room TVST is able to increase the speech intelligibility quality.